Age, genotype and sex effects on growth performance of local chickens kept under improved management in Ghana - Osei-Amponsah, R.; Kayang, B.B.; Naazie, A. (Tropical Animal Health and Production, 2012)
Characterisation of animal genetic resources has been recognised globally as an important step towards their sustainable use. Body weight data of local chickens (213 forest and 160 savannah chickens) and 183 French free-ranging SASSO T44 chickens kept under improved management were collected from hatch to 40 weeks of age and analysed to determine the effects of age, genotype and sex on their growth performance. At all ages, SASSO T44 chickens had significantly (P < 0.05) higher weights (2.6-3.2 kg at 28 weeks) than the local chickens (1.2-1.7 kg at 28 weeks). The rate of growth at the earlier ages in the local genotypes (5.57-7.80 g/day) was lower than the range of 13.81-15.42 in SASSO T44 chickens. Except at hatch, savannah chickens were significantly heavier (P < 0.05) than the forest chickens at all ages. Male chickens had significantly (P < 0.05) superior growth rates than females across all genotypes except from the 20th to the 28th week. Growth trends in both sexes depicted linear increase in body weights; however, the rate of increase in body weights was higher in males as compared to females, thus showing clear sexual dimorphism. There were no significant (P > 0.05) differences in the growth rates of SASSO T44 chickens and local genotypes at the later ages (20-28 weeks). Local chickens from the savannah zone had better growth rate than forest chickens. The significant effect of ecozone on the growth potential of local chickens is an indication that their productive potential could be improved through interventions in the environment such as provision of feed and some veterinary care. © 2011 Springer Science+Business Media B.V.
Keywords: Body weight; Ecozone; Productivity; SASSO T44; Sexual dimorphism